First occurrence of Tupinambis quadrilineatus Manzani & Abe, 1997 (Squamata: Teiidae) in the Amazonian Biome - Ferreira, Leandro Valle; Pereira, Jorge Luiz Gavina; Avila-Pires, Teresa Cristina Sauer; Chaves, Priscilla Prestes; Cunha, Denise de Andrade; Furtado, Camila da Silva (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
We here report the occurrence of Tupinambis quadrilineatus Manzani & Abe, 1997 (Squamata: Teiidae) in the Amazonian biome, in vegetation of savanna situated in southeastern Pará, Brazil. This region has extensive fragments of savanna situated outside any protected area of Pará. T. quadrilineatus was only known from Mato Grosso, Goiás, Tocantins and Minas Gerais states, within the Cerrado biome. This is the first report of the species in savanna in the Amazonian biome and in the state of Pará. This discovery reinforces the idea that knowledge about Amazonian biodiversity is still insufficient. We recommend that new inventories be made in the region and that savanna fragments in southeastern Pará be incorporated into new protected areas.